Coping with prison stress - Buško, Vesna (Array, 1995)
The study examines how prison inmates experience and cope with particular stressful situations, ordinary present during imprisonment. Self-report measures of stress intensity, perceived event controllability, some situational features, and coping mechanisms, were taken in the sample of 453 males incarcerated in several Croatian penal institutions. Canonical discriminant analysis was performed to assess the differences in appraisals and coping mechanisms among 7 groups of subjects formed according to the category of problems selected as most stressful: accommodation, relations with other prisoners, institutional regime, relations with staff, contacts with the outside, vagueness in institution, and health. Three significant discriminant functions accounted for 80% of total intergroup variability of the analyzed set of cognitive appraisal, situational and coping variables. Neither coping mechanisms nor cognitive appraisals, however, were particularly strongly determined by specific stressors as indicated by canonical correlation values and positions of group centroids on derived functions.